Prevalence of myopic retinopathy in rural Central India - Jonas, Jost B. (Acta ophthalmologica, 2017)
Purpose The aim of this study was to determine the prevalence of myopic retinopathy (MR) in rural Central India. Methods The population-based Central India Eye and Medical Study included 4711 subjects (aged 30+ years). The participants underwent a detailed eye examination, including fundus photography. Myopic retinopathy was defined according to the Pathologic Myopia Study Group. Results Readable fundus photographs were available on 4561 (96.8%) subjects (8846 eyes). Myopic retinopathy was present in 15 (0.17 ± 0.04%; 95% confidence interval (CI):0.08%, 0.26%) eyes of 11 (0.24 ± 0.07%; 95%CI: 0.01, 0.04) individuals. Myopic retinopathy occurred only in eyes with an axial length of >26 mm. Eyes with MR had significantly larger optic discs than eyes without MR (3.69 ± 1.22 mm2 versus 2.52 ± 0.77 mm2; p < 0.001). In binary regression analysis, higher prevalence of MR was associated with longer axial length (p < 0.001; odds ratio (OR): 19.6; 95%CI: 4.6, 82.9), higher prevalence of open-angle glaucoma (p = 0.02; OR: 16.1; 95%CI: 1.51, 170), lower best-corrected visual acuity (expressed in logMAR) (=0.03; OR: 0.06; 95%CI: 0.004, 0.75) and female gender (p = 0.002). If level of education was added to the model, educational level was not significantly associated with MR (p = 0.17; OR: 0.53; 95%CI: 0.22, 1.31). If gender was dropped from the model, higher prevalence of MR was associated with lower educational level (p = 0.04; OR: 0.44; 95%CI: 0.20, 0.97). Conclusions Prevalence of MR in rural Central India was low (11/4561 or 0.2%), and correlated with a 16 times higher risk of open-angle glaucoma, after adjusting for axial length and gender. If gender was excluded from the analysis, higher prevalence of MR was associated with lower educational level. This latter finding distinguishes adult MR from today′s school children myopia which is strongly associated with higher educational level.